The Influence of Social Media and E-Wallet Use on Consumptive Behavior Through Lifestyle - Septian Anggaretta, Dhela; Kardoyo; Kusumantoro (Universitas Negeri Semarang, 2025)
Consumptive behavior is an act of excessive and unplanned consumption of goods/services for the sake of lifestyle or desires, not needs. This study aims to analyze the influence of social media and the use of e-wallets on consumptive behavior through lifestyle. This research is quantitative research. The population in this study were FEB UNNES students in the Class of 2022, 2023, and 2024 totaling 4,904. Determination of sample size using the slovin formula with a sample size of 370 respondents. The sampling technique uses propotionate stratified random sampling. Data collection techniques using questionnaires with data analysis techniques include descriptive analysis, path analysis, and Sobel test. The results of this study indicate that social media has a positive effect on consumptive behavior, the use of e-wallets affects consumptive behavior, lifestyle affects consumptive behavior, social media affects lifestyle, the use of e-wallets affects lifestyle, social media affects consumptive behavior through lifestyle, the use of e-wallets affects consumptive behavior through lifestyle. Further research suggestions can add mediating variables that have not been studied such as the use of paylater and QRIS.